Efektivitas Pendampingan Dan Edukasi Gizi Berbasis Pemanfaatan Jus Buah Bit Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Anemia Trimester III Di Wilayah Kerja Puskesmas Kota Rantauprapat - Ratu Hillery; Zulfendri Zulfendri; Agnes Purba (KOLONI, 2026)
Anemia in pregnant women during the third trimester remains a significant public health problem in Indonesia that increases the risk of pregnancy complications, preterm birth, and low birth weight infants. This study aimed to analyze the effectiveness of nutritional counseling and beetroot juice supplementation on increasing hemoglobin levels in anemic pregnant women. A quasi-experimental pretest-posttest control group design was used involving 50 participants divided into experimental and control groups. The intervention consisted of beetroot juice administration combined with nutrition education for seven days, while the control group received standard counseling only. Hemoglobin levels were measured before and after the intervention using a hemoglobinometer. Data were analyzed using a paired t-test with a significance level of p<0.05. The results showed a significant increase in hemoglobin levels in the experimental group compared to the control group. The mean hemoglobin values increased after intervention, with statistical significance of p<0.001. These findings indicate that beetroot juice, rich in iron, folate, vitamins, and antioxidants, supports red blood cell formation. Furthermore counseling and education improved maternal knowledge and behavior regarding anemia prevention. In conclusion, the combination of nutritional counseling and beetroot juice intake effectively increases hemoglobin levels in anemic pregnant women in the third trimester in the working area of Rantauprapat Community Health Center and supports non-pharmacological anemia management strategies in primary care settings implementation framework.